Fatigue Life Prediction of Half-Shaft Using the Strain-Life Method - Xipei Ma; Xintian Liu; Haijie Wang; Jiachi Tong; Xiaobing Yang (Advances in Materials Science and Engineering)
Fatigue life prediction is an important part of the reliability and durability analysis of automobile components. Based on Wang and Brown’s framework, multiaxial random fatigue damage was adopted to predict the fatigue life of half-shaft. The stress analysis of half-shaft was resolved analytically to determine the local stress tensor in the potential area of fracture. The maximum shear strain fatigue damage parameter and the normal stress fatigue damage parameter were evaluated to predict the fatigue life of half-shaft. The results show that the prediction method is reliable and meets the service life and safety requirements.